Pengaruh Sistem Akuntansi Pemerintah Daerah Terhadap Kualitas Laporan Keuangan Daerah pada Badan Pengelolaan Keuangan Aset Daerah (BPKAD) Pandeglang - Verliani - Dasmaran; Tri - Yulaeli; - - Selfiani (Jurnal Akuntansi, 2018)
The purpose of this study was to determine the effect of the application of the Regional Government Accounting System on the Quality of Financial Reports. The research method used is a summative evaluation method, which is a method that emphasizes the effectiveness of the achievement of programs in the form of certain products, and the results of these studies can provide recommendations for future needs. The population in the study are all parts and sub-sections of the BPKAD Pandeglang Regency, and the sample in this study are employees who understand the Regional Government Accounting System totaling 94 people. The sampling technique uses saturated sampling. Recapitulation results from the overall indicators of the Regional Government Accounting System in BPKAD with a score of 85.63% indicate that the Regional Government Accounting System has been implemented very well. And the results of the recapitulation of the overall indicators of the Quality of Financial Statements with a score of 87.14%, this indicates that financial management in the Office of Financial and Asset Management of Pandeglang Regency is very good. The results of the study conclude that the Regional Government Accounting System (SAPD) has a positive and significant effect on the Quality of Financial Statements. Keywords: Regional Government Accounting System, Quality of Financial Statements